KEPUASAN KERJA STUDI KASUS PADA FAKULTAS MIPA UNSYIAH - Eliana Eliana; Banta Karollah; Ferdi Nazirun Sijabat; Intan Novia Astuti; Nasri Zarman (LPPM Universitas Labuhanbatu, 2020)
The purpose of this study was to examine the influence of the work environment, competence and compensation jointly and partially on job satisfaction at the Faculty of Mathematics and Natural Sciences Environment Unsyiah. This research was conducted at the Faculty of Mathematics and Natural Sciences Environment, Unsyiah. The population in this study were employees in the Faculty of Mathematics and Natural Sciences with 72 respondents.This research was conducted using the census method in which the entire population was used as the object of research. The data obtained were then processed using the SPSS 20 analysis tool. This analysis includes the validity test, reliability test, classical assumption test, t test and F test and coefficient of determination (R2). Based on the results show that the work environment, competence and compensation have an effect on job satisfaction. The results of data analysis obtained an R square value of 0.619, which means that the job satisfaction variable can be explained by the work environment, competence and compensation of 61.9%, while 38.1.0% of the effect is explained by other variables. For hypothesis testing (t count> t table), the t test results in this study amounted to (3.554> 1.666) with a significant 0.001 for work environment variables, (3.702> 1.666) and 0.000 significant for competency variables and (2.024> 1.666) and a significance of 0.002 for the compensation variable, the results state that the work environment, competence and compensation have a positive and significant effect on job satisfaction. Whereas for testing the hypothesis together (F count> F table), the results of the F test in this study are (36,884> 3,12) for work environment variables, competence and compensation with a significant 0,000, these results explain that the work environment, competence and compensation has a significant effect on job satisfaction in the Faculty of Mathematics and Natural Sciences Unsyiah.